Formulation of Anti Acne Loose Powder of Bawang Dayak (Eleutherine bulbosa (Mill.) Urb.) Ethanol Extract - Susi Novaryatiin; Nursheilla Rizky Amalia; Syahrida Dian Ardhany (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Bawang dayak (Eleutherine bulbosa (Mill.) Urb is one of the notable Iridaceae family, originating from Central Kalimantan, Indonesia. Previous studies have reported that E. bulbosa ethanol extract and its cream preparation have antibacterial properties that can inhibit the growth of acne-causing bacteria and cause no significant skin adverse reaction. This study aimed to make a loose powder preparation from E. bulbosa ethanol extract and determine its physical evaluation and antibacterial activity. Loose powder formulation was made with various concentrations of E. bulbosa ethanol extract, F0 (0%), F1 (5%), F2 (10%), and F3 (15%). Loose powder evaluates for organoleptic, homogeneity, and antibacterial activity by the disc diffusion method. The results show that E. bulbosa ethanol extract can produce a loose powder formulation. The color of the formula is rather yellow (F0), brown-ash (F1), and light brown (F2 and F3), which has a typical mint odor, smooth texture, and homogeneous. All formulations inhibited the growth of Propionibacterium acnes, Staphylococcus epidermidis, and Staphylococcus aureus. This present study showed the potential of Formula 3 (F3) as an anti-acne loose powder due to its organoleptic properties, homogeneity, and antibacterial activity, which has the largest inhibition zone diameter of 17.6 ± 3.1 mm.